Elucidating the molecular mechanisms for lipoprotein processing and localisation of Factor H binding protein in Neisseria meningitidis - Goncalves da Silva, Ronni Anderson (2020)
Neisseria meningitidis (Nm) is accountable for thousands of meningitis cases that lead to high mortality in children and young adults every year. Currently, as part of the efforts to combat this infectious disease caused by serogroup B strains, two vaccines have been licensed in recent years containing meningococcal lipoprotein Factor H binding protein (FHbp). Trumemba vaccine (Pfizer) has FHbp as its sole antigen and the Bexsero vaccine (GSK) has FHbp as one of four antigens in its vaccine formulation. The success of these vaccine formulations, in particular Trumemba, depends on sufficient surface display of FHbp in order to elicit protective serum antibody response. The expression level of FHbp varies between and within strains and the molecular mechanisms regulating this have been established. The aims of the work presented in this thesis were to elucidate the molecular mechanisms involved in the processing and surface localisation of FHbp, which is key for target recognition following immunisation with FHbp-based vaccines. Firstly, the generation of a transposon (Tn) library in strain MC58 enabled the discovery of the gene responsible for triacylation of FHbp in Nm. The impact of disruption of Lnt, which likely triacylates all other Nm lipoproteins was investigated and the data suggest the potential of Lnt as a novel drug target. Secondly, the identification of single nucleotide polymorphisms (SNPs) in the signal peptide (SP) of FHbp in strain L91543 led to the discovery of unprocessed FHbp on the cell surface and this finding was applicable to others Nm isolates. This has implications for current FHbp-based vaccines. In further detail in Chapter 3, the generation of a Tn library in strain MC58 is described. One mutant that lacked binding to the anti-FHbp monoclonal antibody (mAb) JAR4 was found to have been disrupted in the lnt gene. Experimental evidence was provided to support the predicted role of Lnt in acylating FHbp in Nm. In addition, data are shown that Lnt disruption affects FHbp expression at RNA and protein level suggesting a wider impact on the Nm cell than loss of ability to add the third fatty acid to FHbp. This chapter also presents data concerning the surface exposure of diacylated FHbp in the Lnt mutant which indicates a more flexible Lol machinery in the meningococcus than in E. coli, for which Lnt is essential. Due to the importance of lipoproteins for maintaining membrane integrity and likelihood of Lnt disruption affecting all Nm lipoproteins, it is speculated that the mutant would be significantly affected in membrane homeostasis. This is investigated in Chapter 4. RNAseq analysis of MC58Lnt reveals 183 genes to be DE, including genes encoding lipoproteins and genes related to RNA biology, and involved in adhesion and survival of the meningococcus. The biological impact of Lnt disruption is investigated in adhesion and invasion assays using of HCECs and HUVECs. While the mutant is shown to invade HCECs less, it invaded HUVECs more than when compared to the WT. HCECs and HUVECs also presented different pattern of expression of IL-6 and IL-8. HUVECs expressed more of these inflammatory proteins and this was suggested to be linked with higher invasion of MC58Lnt in this type of cells. Whereas survival and replication in THP-1 cells by the mutant was not affected, it displayed reduced ability to form biofilms on an abiotic surfaces and reduced virulence in the tested Galleria mellonella model. Importantly the disruption of Lnt leads to increased susceptibility of Nm to several antibiotics tested, supporting the potential of Lnt as a novel drug target. To further investigate molecular mechanisms that govern FHbp processing and surface localisation, the rest of the thesis is focused on the SP of FHbp. In Chapter 5, strain L91543 containing SP SNPs is taken for analysis. Site-directed mutagenesis (SDM) shows that these SNPs in the SP of FHbp are indeed responsible for processing and surface localisation. Specifically, a single SNP in the hydrophobic region of the SP, common to 88% of the UK isolates analysed (1742/1895), abolishes FHbp processing. This has important implications for Trumemba which consists of acylated FHbp. We show by FACS reduced display of FHbp in strains with SP SNPs and corresponding reduced susceptibility to killing by FHbp-specific antibodies in SBA assays.